THE ASSOCIATION BETWEEN AUTONOMIC NERVOUS SYSTEM DYSFUNCTION AND MENSTRUAL DISORDERS IN FEMALE ADOLESCENTS: A MULTIDISCIPLINARY EVALUATION - Kenzhaeva Dilfuza Kuvatovna; Abdullayeva Nargiza Nurmamatovna; Djurabekova Aziza Takhirovna (Scholar Express Journals, 2025)
Adolescence represents a critical period of physiological and psychological development, marked by significant hormonal fluctuations and the maturation of various body systems, including the autonomic nervous system (ANS) and reproductive function. During this transitional phase, the complex interplay between neurological and endocrine systems becomes particularly evident, with emerging evidence suggesting that autonomic nervous system dysfunction may play a significant role in the development and persistence of menstrual disorders among female adolescents.
Keywords: autonomic dysfunction; menstrual cycle